Software Services Export and Its Implications on Economic Growth in India: An Empirical Study - Mousumi Bhattacharya; Sharad Nath Bhattacharya (Economic Review: Journal of Economics and Business, 2013)
The structural shift in India's services export since 2003-04 may be attributed to rapid expansion in international trade and investment facilitated by an increased liberalization and the use of technology. The study aims to investigate the possible co-integration and the direction of causality between software services export and non-software miscellaneous services (business, financial, communication and other miscellaneous) export and economic growth during the period 2000-01:Q1-2008-09:Q4. Granger Causality Test conducted in a Vector Error Correction Model (VECM) framework revealed unidirectional causality from software services export to economic growth. To investigate the long and short run dynamics among the variables impulse response analysis is also done.
Keywords: F43; O14; 330; VESM; cointegration; granger causality; software export